Micropatterning: Interdigitated Multicolored Bioink Micropatterns by Multiplexed Polymer Pen Lithography (Small 19/2013). Issue 19 (4th October 2013) - Brinkmann, Falko; Hirtz, Michael; Greiner, Alexandra M.; Weschenfelder, Markus; Waterkotte, Björn; Bastmeyer, Martin; Fuchs, Harald
<x xml:space="preserve">Abstract</x> Multi‐colored micropatterns are created by M. Hirtz, H. Fuchs, and co‐workers on page 3266 using multiplexed polymer pen lithography (PPL). Separated macroscopic areas on a polymer pyramid stamp are coated with different inks. Taking advantage of the spatial control and capability of precise registry in PPL, truly multiplexed micropatterns with the different inks interdigitated within each repetitive subpattern are created over large areas. Due to the mild process parameters, this technique is especially of interest for biologicallyactive substances. Artwork in main image courtesy of G. Brinkmann. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>